Idrott och historiebruk - exemplet idrottshistoriske föreningar i Sverige - Lindroth, Jan (Forum for Idræt, 2002)
To aspekters nære kobling - præstationsfokusering og organisationshistorie. Sport and the uses of history – examples from Sweden In contrast to Denmark, there is a strong tradition in Sweden for associations of sporting history. For this reason, the editors asked professor Jan Lindroth to give us an introduction to Swedish sporting associations. What is an association of sporting history? How did they originate? How are they organised? What are their activities? Associations of sporting history sprang up during the 1970’s and since then the majority of Sweden’s ‘lä’ (counties) have acquired an association, so that today there exist over 20 associations of sporting history. Most of these associations have their base in organisations devoted to the sporting movement. The activities of these associations centre particularly around meetings and around publications such as newsletters, but over and above that they are involved in interviews with sporting veterans, with 156 the collection of material, of literature and equipment, and with exhibitions and sporting museums or memorial sites. Seen from a distance, associations of sporting history exemplify the potential to employ history in the service of a common identity and nostalgia.